Evaluation of the relation between adenoids hypertrophy and cranial base angles - Dalili Z; Rahro Taban S; Vahedi MA (Tehran University of Medical Sciences, 2006)
Background and Aim: Adenoids are normally large in children and their size starts to reduce during adolescence. Hypertrophic adenoids could be associated with allergic reactions. Enlarged adenoids result in nasal breathing difficulties and the child is forced to switch to mouth breathing. Airway obstruction causes postural alterations of jaw, tongue and head, and due to persistent obstruction, patient's appearance changes to adenoid face. Evaluation of nasopharyngeal space in lateral cephalometic view is a simple and repeatable method for determination of the size and shape of adenoids and nasopharyngeal space which can provide a simple measurement of nasopharyngeal obstruction. The roof of nasopharyngeal space is covered by the sphenoid bone. Thus changes of nasorespiratory resistance by hypertrophic adenoids may affect the cranial base angles. In this study, the relationship between adenoid hypertrophy and cranial base angles was investigated. Materials and Methods: In this descriptive-analytic study, lateral cephalometric views of 7 to 14 y/o patients from the files of orthodontic centers in Rasht city were selected. The radiographs with proper resolution were separated for this research. Adenoid to nasorespiratory ratio (A/N Ratio) was determined by Fujioka method and categorized in three groups: A (A/N 0.8), B (0.5<A/N<0.8) and C (A/N 0.5) by trained maxillofacial radiologist. Then cranial base angle (NSAr) on lat cephalometric view was measured and categorized to normal, wide and narrow. Gonial angle, sum of articular, gonial & saddle angle, posterior to anterior facial height ratio and facial skeleton classification were also determined. Data were analyzed using Chi-Square and Pearson tests with p<0.05 as the limit of significance. Resuts: After evaluation of 206 lateral cephalometric views, adenoid hypertrophy (A and B groups) was observed in 66% of cases whereas 34% were normal. The frequency of narrow, normal and wide cranial base angles in lateral ceph views was 28%, 30% and 42% respectively. There was significant difference among different cranial base angle regarding the presence or absence of adenoid hypertrophy (P<0.001). According to Pearson coefficient, there was significant relation between A/N ratio groups and different cranial base angles (R=0.2). Conclusion: Based on the results of this study, little correlation exists between A/N ratio and cranial base angle. Further studies are recommended to investigate the possible effects of other factors such as genetics and the environment.